2022
DOI: 10.1039/d1se02052h
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect between PPy:PSS copolymers and biomass-derived activated carbons: a simple strategy for designing sustainable high-performance Li–S batteries

Abstract: An activated carbon from the seed of an avocado, a fruit highly and increasingly demanded by consumers, has been used as a sulfur host for lithium sulfur (Li–S) batteries. Although...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 96 publications
(98 reference statements)
3
8
0
Order By: Relevance
“…For a proper comparison, the graphs in Figure 7a, Figure 7b and Figure 7c take into account the four SOC discussed previously, that is, upon first and second reduction processes (1 and 2 in inset) and after the two charge stages (3 and 4 in inset) for CV, EIS and GITT, respectively. Relevantly, the figure shows the dependence of D Li + trends and values on the employed technique: hence, D CV ranges between 10 À 7 and 10 À 8 cm 2 s À 1 , as indeed observed in previous reports, [90,91] while D EIS varies with one order of magnitude lower range between 10 À 8 and 10 À 9 cm 2 s À 1 , and D GITT surprisingly shows a much wider interval between 10 À 6 and 10 À 12 cm 2 s À 1 . This notable variability may be ascribed to intrinsic characteristics of the various techniques, as observed in a previous work focusing on insertion materials.…”
Section: Chemsuschemsupporting
confidence: 86%
“…For a proper comparison, the graphs in Figure 7a, Figure 7b and Figure 7c take into account the four SOC discussed previously, that is, upon first and second reduction processes (1 and 2 in inset) and after the two charge stages (3 and 4 in inset) for CV, EIS and GITT, respectively. Relevantly, the figure shows the dependence of D Li + trends and values on the employed technique: hence, D CV ranges between 10 À 7 and 10 À 8 cm 2 s À 1 , as indeed observed in previous reports, [90,91] while D EIS varies with one order of magnitude lower range between 10 À 8 and 10 À 9 cm 2 s À 1 , and D GITT surprisingly shows a much wider interval between 10 À 6 and 10 À 12 cm 2 s À 1 . This notable variability may be ascribed to intrinsic characteristics of the various techniques, as observed in a previous work focusing on insertion materials.…”
Section: Chemsuschemsupporting
confidence: 86%
“…Porous carbon are broadly applied to enhance the capability of Li-S batteries by adjusting pore structure, surface chemistry and other properties. Extensive literature reports have indicated that the polysulfide dissolution can be inhibited by increasing the contact between sulfur and conductive matrix by employing porous carbon materials having large surface area ( Luna-Lama et al, 2022 ; Ma et al, 2022 ). Depending on the size of the pores, there can be three types of porous carbon namely, macroporous, microporous and mesoporous with each having different effect on the Li-S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: liuyong209@haust.edu.cn; zhangwh@haust. edu.cn cathodes, [40][41][42][43][44][45][46][47][48][49]260 insertion of an interlayer between the cathode and separator, [50][51][52][53] and optimization of the electrolyte. [54][55][56] Among them, sulfur cathode modication has received substantial attention because it increases the conductivity of the sulfur cathode, connes LiPSs in the cathode, and alleviates the volume expansion of the sulfur cathode during cycling.…”
Section: Introductionmentioning
confidence: 99%